MINUTES OF THE TOBACCO INDUSTRY MEETING ON DOWNUNDER (Tufts Archival Research Center, 2007)
Minutes of the tobacco institute on operation downunder on March 2nd, 1988. Discusses the pros and cons of downunder. Identifies benefits of the program as aligning the tobacco industry with more moderate popular allies, allows the industry to legislatively protect against smoker discrimination and provides a place for smokers to feel more comfortable (separate sections). Identifies the cons of the program as problems defining what "separate" means, the legislative problems the industry could possibly be open to, and possibly appearing "weak" by making concessions. Reports alternative plan suggested by RJR and details the strategy to pursue it.